2020
DOI: 10.1002/pa.2447
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of population, urban agglomeration, and economic growths in Sub‐Saharan Africa: Evidence from panel data

Abstract: This study analyses population, urban agglomeration (UAG), and economic growths dynamics in Sub‐Saharan Africa (SSA) using the World Bank panel data ranging from 1970 to 2019. The study utilized a panel fixed effect (FE) model after verifying the suitability of the model using a Hausman test. The estimation result from the panel FE model reveals remarkable findings which conform to some extent, the theoretical a priori expectations. The result shows that growth in rural as well as urban population growth and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In contrast to the overall population, it is observed that the urban population exerts a noteworthy and adverse influence on the economic growth of G20 nations. One plausible hypothesis for the adverse effects of urban population on GDP growth is the insufficient alignment between the growth rate of the urban population and the corresponding expansion in production and food supply, as well as the accessibility of fundamental necessities such as clean water, food, healthcare, and educational facilities [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the overall population, it is observed that the urban population exerts a noteworthy and adverse influence on the economic growth of G20 nations. One plausible hypothesis for the adverse effects of urban population on GDP growth is the insufficient alignment between the growth rate of the urban population and the corresponding expansion in production and food supply, as well as the accessibility of fundamental necessities such as clean water, food, healthcare, and educational facilities [65].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might lead to a rise in prices and a decrease in savings. The limited availability of savings and investment impedes the promotion of economic development [65].…”
Section: Discussionmentioning
confidence: 99%
“…Ahrend et al [56] also proved a positive relationship between urban agglomeration and economic growth for OECD regions. Asowga et al [57] found a positive association between urban agglomeration and economic growth for a panel of sub-Saharan African countries during 1970-2019. Jayasooriya [58] also demonstrated a positive association between urban agglomeration and economic growth for regions in China using a GMM method during 2004-2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Spatio-temporal patterns of urban growth are examined and compared with the assumptions of urbanization models (diffusion-agglomeration and three growth patterns). This is achieved through the analysis of time-series neighborhoodlevel built-up area densities, aiming to identify two broad spatial scales of cities [15]. Economic agglomeration is assessed via spatial econometric modeling, evaluating the economic and technological indicators of urban agglomeration [16].…”
Section: Introductionmentioning
confidence: 99%